A Review of Food-Based Dietary Guidelines: Are Iconographies Representing Sustainability? - Ornella Tiboni-Oschilewski; Beatrice Biasini; Alice Rosi; Francesca Merloni; Benedetta Merloni; Francesca Scazzina (Proceedings)
Background and objectives: The food-based dietary guidelines (FBDGs) are primarily intended to promote healthy diets, and little is known about specific references to the multidimensional aspects of sustainability in their iconographies. Therefore, the objective of this study is to review the existing FBDGs iconographies according to the four sustainability dimensions (nutrition-health, socio-cultural, environmental, and economic) and evaluate to what extent these tools include different sustainability indicators. Methods: FBDGs were collected from the FAO repository and government’s official websites in January 2023. Only the latest FBDG editions targeting the general population were included in the study. Non-governmental iconographies addressing macrogeographical areas were also analysed. Sustainability indicators (n = 30) were chosen from a preliminary literature review from the four sustainability dimensions. Visual analysis was performed. Results: In total, 191 iconographies were found. The health dimension was the most represented, being present in all iconographies with at least one indicator, followed by the socio-cultural dimension. The environmental dimension was present in 29.8% of the iconographies, while the economic dimension was the least mentioned (1.6%). Globally, the main health indicators were diet diversity (99%), healthy lifestyle (79%), and the avoidance of critical nutrients (71%). Culinary practices (76%) and traditional products (71%) were the most represented within the socio-cultural pillar. Only three iconographies included affordability/costs to consumer as an economic indicator. Those indicators that no iconography mentioned were related to food consumption outside the home, gender, migrants, and fair trade. The more recent the iconography, the greater the presence of sustainability dimensions and indicators. Higher-income countries had a greater presence of health and environmental sustainability indicators, while lower-income countries highlighted more socio-cultural and economic aspects. Discussion: These results are consistent with those retrieved from the literature analysing the main FBDG documents, but present new and complementary information. As the practicality, affordability, availability, and access to healthy and sustainable foods are the main barriers to compliance with dietary guidelines, more focus should address these factors. These results offer an opportunity for technicians and policymakers for adding more sustainability aspects to improve the iconographies while keeping them easy and intuitive.